Negotiating Tradition and Modernity: Malam Satu Suro Ritual as a Cultural Identity Practice among Javanese Migrants in Bangun Rejo Village, South Kalimantan - Noor Hasanah; Muhammad Azmi Hidayat (Yayasan Azhar Amanaa Yogyakarta, 2026)
The Malam Satu Suro ritual remains one of the enduring cultural traditions practiced by Javanese migrant communities in Bangun Rejo Village, South Kalimantan, despite rapid social transformation and modernization. Existing studies have largely focused on the ritual's symbolic meanings and religious dimensions, while limited attention has been paid to its role in sustaining cultural identity and negotiating tradition within a multicultural environment. This study aims to examine how the First Suro Night ritual functions as a cultural identity practice and explores the ways local communities negotiate traditional values in the context of contemporary social change. Employing a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews with community leaders, religious figures, and residents, as well as document analysis. The findings reveal that the ritual serves not merely as a ceremonial event but as a cultural mechanism for preserving Javanese identity, strengthening social cohesion, and transmitting local wisdom across generations. At the same time, the tradition demonstrates a dynamic process of adaptation, in which cultural practices are continuously reinterpreted to align with Islamic values and the realities of modern life without losing their essential cultural significance. This study contributes to discussions on cultural resilience, identity negotiation, and the preservation of intangible cultural heritage in Indonesia's multicultural society.